Black Phosphorus Nanostructure Based Highly Sensitive and Selective Surface Plasmon Resonance Sensor for Biological and Chemical Sensing: A Review. (2nd January 2023) - Nangare, Sopan; Patil, Pravin
Abstract: Surface plasmon resonance (SPR) is an attention-grabbing sensor type, which offers the sensitive and selective detection of biomolecules and environmentally toxic substances. Notably, the SPR sensor gives excellent rewards including real-time, in-situ, and label-free measuring capability as compared to existing sensing technologies. As a result, these noteworthy merits of the SPR sensor make it straightforward to investigate the molecular events and chemical/gas molecule interaction. Unfortunately, there are different binding events including smaller molecular mass substances, which cannot be detected at the SPR sensor. Accordingly, this downside of the SPR sensor eventually led to the design and implementation of new approaches for sensitivity and selectivity improvement for sensing applications in different fields. Recently, the black phosphorus (BP) derived 2 D nanomaterial is stand out as a distinctive nanostructure in comparison to recently reported other 2 D nanomaterials. Substantial and functional characteristics of BP including simplicity of operation, optical properties, high carrier mobility, stronger immobilization of receptors and biomolecules, electronic bridging playing important role in the highly selective and sensitive assessment of analyte. The designed BP nanostructures are mostly serving to accelerate the plasmon material signals followed by improved molecular sensing that may due to 40-times faster-sensing responses of BP nanostructure than reported 2 D nanomaterials. Therefore, the present review article sheds light on the latest significant advances in biological and toxic gas detection through 2D BP nanostructures based SPR sensors. In the future, this review will facilitate detailed insights into the development of BP-based groundbreaking frameworks for highly sensitive and selective recognition of biomolecules and environmental pollutants. Graphical Abstract: